Fundamentals of diagnostic ultrasonography in sheep and goat medicine: a comprehensive illustrated overview - Marzok, Mohamed; Tharwat, Mohamed (Frontiers in Veterinary Science, 2025)
This illustrated review emphasizes the fundamentals of diagnostic ultrasonography in sheep and goat medicine. The procedure can effectively assess the thoracic and abdominal organs in both healthy and diseased states. The review discusses five main sections. The first one clarifies the principles of pulmonary sonography in sheep and goats followed by image finding in animals with respiratory disorders including pneumonia, pleuropneumonia, lung abscessation and pleuritis. Second section shows the fundamentals of echography in sheep and goats followed by scanning of animals with cardiovascular disorders including heart failure, fibrinous pericarditis, endocarditis and nutritional muscular dystrophy. Third section of this review discusses the principles of gastrointestinal sonography in sheep and goats followed by picture in some digestive disorders including peritonitis, enteritis and retroperitoneal abscessation. Fourth part shows the basics in hepatic and biliary tissue followed by sonography of sheep and goats with hepatic and biliary disorders including fatty liver, hepatitis cysticercosis, cholangitis, cholecystitis, cholestasis and choledocholithiasis. Last section of this review discusses the fundamentals of urinary system ultrasonography followed by imaging of the urinary disorders including renal failure, hydronephrosis, pyelonephritis, obstructive urolithiasis, cystitis and paralysis of the urinary bladder. In conclusion, ultrasonography of either healthy or diseased sheep or goats is very useful for assessing the normal structure and function of both healthy and dysfunctional organs. It is highly recommended to adopt this procedure as a standard preliminary method for examining sheep and goats with any medical condition.